2011
DOI: 10.1007/s10096-011-1164-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil CD64: diagnostic accuracy and prognostic value in patients presenting to the emergency department

Abstract: Purpose: To evaluate the diagnostic accuracy and prognostic value of neutrophil CD64 expression for bacterial infection in febrile adult patients presenting to our hospital emergency department. Methods:We prospectively included 132 patients with with fever ≥38º C (≥100.4º F) during the last 24 hours and we did the measurement of CD64 on neutrophils the day after the admission of the patient at the emergency department. We followed the patients until the full recovery or death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
2
19
1
2
Order By: Relevance
“…CD64 expression on neutrophils was found useful in previous studies for the prediction of mortality (Cid et al, 2011;Danikas et al, 2008;Livaditi et al, 2006); however, in our study, it showed an accuracy of 65% in predicting survival, which was lower than that of SAPS II (91%) and SOFA (80%) score. SAPS II was also identified by multivariate analysis as an independent predictor of mortality, underlying its importance in the identification of severely ill patients (Vincent, 2008b).…”
Section: Discussioncontrasting
confidence: 84%
“…CD64 expression on neutrophils was found useful in previous studies for the prediction of mortality (Cid et al, 2011;Danikas et al, 2008;Livaditi et al, 2006); however, in our study, it showed an accuracy of 65% in predicting survival, which was lower than that of SAPS II (91%) and SOFA (80%) score. SAPS II was also identified by multivariate analysis as an independent predictor of mortality, underlying its importance in the identification of severely ill patients (Vincent, 2008b).…”
Section: Discussioncontrasting
confidence: 84%
“…These findings are in agreement with previous studies. 11,12 Similar results have been reported in adults by Cid et al 13 who revealed that patients with sepsis had a greater number of circulating CD64 positive PMNs (mean 71%) than in healthy controls (mean 19%).…”
Section: Discussionsupporting
confidence: 77%
“…The CD64 index has been suggested to be predictive of positive bacterial cultures and a useful test for management of sepsis and other significant bacterial infections [67]. Another study demonstrated that the CD64 index is higher in febrile adult patients with bacterial infections, with a sensitivity of 87% (95% CI: 79-92%), and that high CD64 expression is related to survival [68]. In contrast, it has been reported that CD64 indices greater than 2.2 are specific (89% specificity [95% CI: 83-94%]) but less sensitive (63% sensitivity [95% CI: 55-71%]) to predict bacterial infections in critically ill patients [69].…”
Section: Biomarkers Of Sepsismentioning
confidence: 99%